Landscape of Serotypes Pneumococcus Isolate with Pneumococcal Meningitis in the Russian Federation - G. V. Beloshitsky; I. S. Koroleva; M. A. Koroleva (Эпидемиология и вакцинопрофилактика, 2015)
Invasive pneumococcal serotypes landscape in various Russian regions studied. The study showed dominance (in decreasing order of importance) serogroups/serotypes 3, 6, 19, 4, 23, 18, 14, 15, 7, 11 and 9, which accounted for 88% of all identified serogroups/ serotypes. Among children under 5 years occupied a leading position serogroups/serotypes 19F, 18, 14, 6, 3, 7F and 23F, whereas among adults older than 45 years was dominated by serogroup/serotype 3, 6, 19F, 11, 4, 18, 23, 7, 15 and 14. The most frequently encountered material samples sectional serotypes 4, 23F, 14, 11A, 19F and 3.